Overview and considerations for the reporting of clinical pathology interpretations in nonclinical toxicology studies. (25th September 2019) - Aulbach, Adam; Vitsky, Allison; Arndt, Tara; Ramaiah, Lila; Logan, Michael; Siska, William; Cregar, Laura; Tripathi, Niraj; Adedeji, Adeyemi; Provencher, Anne; Gupta, Ara; Jordan, Holly; et al.
Abstract: Clinical pathology reporting practices are diverse among individuals and organizations involved in nonclinical toxicology studies. Clear, informative, and consistent reporting of clinical pathology results increases their value and avoids misinterpretation, resulting in decreased drug development costs. In recent years, certain common practices in clinical pathology reporting have been embraced by industry leaders and more consistently utilized across the pharmaceutical industry. The purpose of this manuscript is to review current clinical pathology reporting practices and to provide nonbinding suggestions to improve consistency, quality, and value of clinical pathology reports generated in support of nonclinical toxicology studies.